Evaluasi Efektivitas Program Pembinaan Gelandangan dan Pengemis (GEPENG) di Dinas Sosial Kota Pekanbaru - Alvira Jihan Arista; Sitti Rahmah (Al-Manar Journal of Public Administration and Management, 2025)
Addressing the issue of vagrants and beggars (GEPENG) in urban areas poses a significant challenge for local governments, including the Social Service of Pekanbaru City. To tackle this problem, the Social Service of Pekanbaru City has implemented a guidance program aimed at social rehabilitation, economic empowerment, and social reintegration of vagrants and beggars. This study aims to evaluate the effectiveness of the guidance program at the Social Service of Pekanbaru City based on indicators such as the reduction in the number of vagrants and beggars, the success of social rehabilitation, skill enhancement, and its impact on the social and economic lives of the participants. The study employs a qualitative approach, using in-depth interviews, observations, and documentation for data collection. The evaluation results indicate that the guidance program has successfully reduced the number of vagrants and beggars in Pekanbaru. However, significant challenges remain in terms of program sustainability, difficulties in social reintegration, and limited resources for skill training and economic empowerment. Factors affecting the program's effectiveness include budget constraints, social stigma towards vagrants and beggars, and a lack of community support in reducing the practice of giving money to beggars on the streets. The study recommends increasing the budget, strengthening collaboration among relevant parties, and providing more intensive support for participants after the guidance program.